2019
DOI: 10.1002/gj.3595
|View full text |Cite
|
Sign up to set email alerts
|

Major, trace, and REE geochemistry of the Meghna River sediments, Bangladesh: Constraints on weathering and provenance

Abstract: The major, trace, and rare earth element (REE) compositions of sediments from the Meghna River in Bangladesh have been examined to infer their sediment type, compositional maturity, chemical weathering intensity, provenance, and tectonic setting.Geochemically, the sediments are classified as litharenites, shale, and wacke. The ICV (Index of Compositional Variability) values (0.92 to 1.10) indicate that the sediments have low compositional and mineralogical maturity. Major and trace element abundances display m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 64 publications
(242 reference statements)
1
45
0
1
Order By: Relevance
“…Recycled sources typically represent quartzose sediments from a mature continental provenance, with the derivation of the sediments likely from a highly weathered granite-gneiss terrain and/or from a pre-existing sedimentary terrain such as in the southern Himalayas [13,37]. Similar results were obtained for Miocene Surma Group sandstones in the Bengal Basin by Rahman and Suzuki [37], for Brahmaputra-Jamuna River (BJR) sediments by Bhuiyan et al [7] and for Ganges-Brahmaputra (GBR) sediments (data reported in Hossain [9]).…”
Section: Major Elementssupporting
confidence: 66%
See 4 more Smart Citations
“…Recycled sources typically represent quartzose sediments from a mature continental provenance, with the derivation of the sediments likely from a highly weathered granite-gneiss terrain and/or from a pre-existing sedimentary terrain such as in the southern Himalayas [13,37]. Similar results were obtained for Miocene Surma Group sandstones in the Bengal Basin by Rahman and Suzuki [37], for Brahmaputra-Jamuna River (BJR) sediments by Bhuiyan et al [7] and for Ganges-Brahmaputra (GBR) sediments (data reported in Hossain [9]).…”
Section: Major Elementssupporting
confidence: 66%
“…This is consistent with previous compositional and mineralogical results reported by Rahman et al [16] who determined the Brahmaputra sediments contained a significant amount of quartz (60%-65%), along with feldspar (5%-8%) and rock fragments and/or mafic minerals (30%-40%). Similar geochemical studies of clastic sediments from the Meghna [9] and Brahmaputra [7] rivers also indicated the sediments were primarily lithic arenites with SiO2 contents ranging from 58-80 wt.% SiO2 and with quartz contents of around 65%. The classifications arising from the major element ratio plots emphasizes the relative chemical and mineralogical immaturity of the Brahmaputra sediments, with none being classified as mature quartz arenite by either scheme.…”
Section: Major Elementsmentioning
confidence: 61%
See 3 more Smart Citations